Development of Russophile and Narodovetsky Movements in Transcarpathia - Стряпко, Іван Стряпко (Poznańskie Studia Slawistyczne, 2015)
The article researches a development of the national-cultural movements. The attention is paid to the development of Russophiles and its organizational center „Organization of Saint Vasyl the Great”. Author describes the discussion among Transcarpathian intellectuals regarding the use of Russian language. The refusal of Russophilism by the part of intellectuals led to the development of Narodovetskyy movement. The author explains this process as a stage before development of Ukrainophile movement.